Integrated Marketing Communication (IMC) Islamic Business Ethics Perspective - Cucu Komala (Khazanah Sosial, 2020)
The purpose of writing this article is to find out Integrated Marketing Communication (IMC) based on Islamic ethics. The Islamic ethics referred to is based on the ethics exemplified by the Prophet Muhammad. This research method is a descriptive qualitative method with a literature study approach sourced from journals, articles, and other sources. The success of the Prophet in business is a prototype in doing business. The key to Rasulullah's business stems from building good communication with consumers promoting Islamic values in product recognition, pricing, promotion and places such as honesty, trustworthiness, fairness, upholding consumer rights as product buyers. Honesty is an important capital, what is promoted must be by the goods presented with price controls should not be excessive, and price-fixing is prohibited.